2004
DOI: 10.1111/j.1651-2227.2004.tb02637.x
|View full text |Cite
|
Sign up to set email alerts
|

How do paediatricians communicate with children and parents?

Abstract: Aim: The outpatient clinic visit is the major focus of the hospital medical process for most paediatricians, children and parents. The importance of children as active participants in this interaction has been recognized. Our study aims are to describe and assess the components of doctor‐parent‐child communication in the outpatient setting. Methods: Fifty‐one medical paediatric clinic consultations were recorded on audio cassette, and communication was analysed according to quantitative methods. Questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
3
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 18 publications
2
53
3
11
Order By: Relevance
“…21 Interestingly, two of the studies showed that when the children did speak more in the consultations, the consultations were not longer, rather the child took up the adult's discourse space. 31,36 Limitations of studies included in the review A number of methodological limitations were identified in the studies found for this review.…”
Section: Research Exploring Why the Child Has Limited Involvementmentioning
confidence: 99%
See 3 more Smart Citations
“…21 Interestingly, two of the studies showed that when the children did speak more in the consultations, the consultations were not longer, rather the child took up the adult's discourse space. 31,36 Limitations of studies included in the review A number of methodological limitations were identified in the studies found for this review.…”
Section: Research Exploring Why the Child Has Limited Involvementmentioning
confidence: 99%
“…[18][19][20][21]24,26,29,31,36 These studies use different methods to reach these estimates and so are not directly comparable with one another. However, they do show that the child has a limited quantifiable involvement in their own consultation.…”
Section: The Quantitative Amount Of the Child's Involvementmentioning
confidence: 99%
See 2 more Smart Citations
“…Health communication may be perceived as a relational process of exchanging information and its understanding between at least two people, including contextual variables and individual characteristics (Araújo & Cardoso, 2007;Arora, 2003;Fisher & Broome, 2011;Wassmer et al, 2004). In some cases of health services, such as pediatric assistance, communication occurs necessarily between the health professional, patient and caregiver, a triadic interaction that requires specific abilities from pediatricians (Gabe, Olumide, & Bury, 2004;Howells, Davies, & Silverman, 2006;Howells & Lopez, 2008;McGraw et al, 2012;Nobile & Drotar, 2003;Tates & Meeuwesen, 2001).…”
mentioning
confidence: 99%